Ultralong ZnO/Pt hierarchical structures for continuous-flow catalytic reactions. (5th November 2016) - Zhang, Wei; Wang, Gang; He, Zhongyuan; Hou, Chengyi; Zhang, Qinghong; Wang, Hongzhi; Li, Yaogang
Abstract: Grass-like double-layer ZnO micro-nanostructures in the confined microchannels is fabricated via fluid construction methods, with the vertical height as high as 50 μm. Subsequently, surface modification of Pt solutions produced uniformly distributed catalytic Pt micro-nanostructures in a facile method. The efficiency of the grass-like catalysts was demonstrated for the continuous reduction reaction of o -nitrophenol and degradation methylene blue. Reaction rates and yields were significantly enhanced and the catalytic structures were recyclable. The results should be significant upon current microfluidic technologies, and exhibit great potentials in continuous flow reactions. Graphical abstract: Highlights: ZnO/Pt hierarchical structures were achieved in confined microchannels. ZnO/Pt hierarchical structures were achieved via a facile and continuous fluid process. Larger surface provided much more ZnO/Pt heterostructures. Ultralong structures accelerated the process of mass and heat transfer.